Factores que limitan la atención prenatal en gestantes atendidas en el Centro de Salud Santiago, Ica 2022 - Cajamarca Huaripaucar, Carolina Rosa (2024)
Se realizó un estudio con el objetivo de determinar los factores que limitan la atención prenatal en gestantes atendidas en el Centro de salud Santiago, Ica 2022. Estudio descriptivo simple, prospectivo de corte transversal; nivel de investigación cuantitativo y diseño no experimental. La muestra la conformaron 150 gestantes. Factores institucionales: 55.3% considera que el personal no está capacitado, 54.7% tiene un trato amable o de calidad, 50.70% se mostró conforme con los horarios de atención, el tiempo de espera fue entre 10 a 20 minutos (37.30%). Factores geográficos: el tiempo que le tomo llegar a la gestante al Centro de Salud fue entre 10 y 30 minutos (37.30%), proceden de la zona urbana un 54.0%. Factores personales: 37.30% no recibe apoyo familiar o de su pareja para asistir a sus atenciones, el 28.00% que es el tiempo que toma acudir a los controles, el 25.30% indicó que es el miedo, el 24.70% que es por el poco permiso del trabajo y el 22.00% que la poca empatía por parte del personal de Salud, 60.00% sí muestra temor al acudir al Centro de Salud de Santiago, el 49.30% tiene vergüenza. Factores económicos: el gasto aproximado al acudir a una atención de más de 6 soles con 36.00%, siendo el ingreso mensual entre S/.950 y S/.1200 (36.0%), los factores que limitan la atención prenatal en el centro de Salud Santiago son los institucionales, personales, geográficos y económicos. ----- A study was carried out with the objective to determine the factors that limit prenatal care in pregnant women attended at the Santiago Health Center, Ica 2022. The type of study was correlational, retrospective and cross-sectional; the research level was quantitative and non-experimental design. The sample was made up of 150 pregnant women who attended at the Santiago Health Center, Ica 2022. Institutional factors: 55.3% consider that the staff is not trained, 54.7% have a friendly or quality treatment, 50.70% were satisfied with the service hours, the waiting time was between 10 to 20 minutes in 37.30%. Geographical factors: the time it takes the pregnant woman to reach the Health Center is between 10 and 30 minutes in 37.30%, 54.0% come from the urban area. Personal factors: 37.30% do not receive family or partner support to attend their care, 28.00% that is the time it takes to go to the controls, 25.30% indicated that it is fear, 24.70% that it is because of the little work permit and 22.00% that the little empathy on the part of the health personnel, 60.00% do show fear when going to the Santiago Health Center, 49.30% are ashamed. Economic factors: the approximate expense when attending care of more than 6 soles with 36.00%, with the monthly income being between S/.950 and S/.1200 at 36.0%, the factors that limit prenatal care at the Santiago Health Center are institutional, personal, geographical and economic. There is a significant relationship between institutional factors (p<0.05), geographic factors (p<0.05), personal factors (p<0.05) and economic factors that limit prenatal care in pregnant women attended at the Santiago Health Center, Ica 2022.